The Effect of Use Passive Portfolio Management Strategy on The Efficient Portfolio of Common Stocks Application Study in Iraq stock market - علي جيران عبد علي; احمد جبار كعيد (Iraqi Journal for Administrative Sciences, 2024)
The Present Study Tries to Show the phases of the investment portfolio which took important role in investment studies and took various shapes and forms. This requires specification of its elements and types, focusing on some of these types which have specific importance in investment. In this study I focused to use one of the strategies of investment portfolios. It is the strategy of a passive shares portfolio in the Iraq stock market financial. Can "the use of passive management strategy lead to the selection of portfolio stocks using the cursor track strategy simulation to outperform the full performance of the governor of ordinary shares used one of the Basic standards for active management"? I used the monthly data of the shares to (23) companies samples that listed in Iraq stock market from (2012-2016) supposing the using of active management method and alpha, beta criteria, the expected profit average, number of transactions which lead to improve the features and performance of portfolio and measuring this performance. The study had concluded to a number of conclusions (the choosing the passive management portfolio according to high Liquidity criteria will improve the features of the portfolio). I recommended choosing this strategy.